Pengembangan Buku Ajar Penanganan dan Terapi Cedera Olahraga - Rahmat Sanusi; Fadli Surahman; Hilda Oktri Yeni (Journal Sport Area, 2020)
The aim of this research is generating a text book of treatment dan injuries therapy in sports for students of physical education and recreation program at Karimun University. The study is a research of developing that refers to Borg and Gall desain that involving four validators, those are lecture as user, therapist, masseur dan media expert. Small-scale testing involves 10 students and large-scale testing involves 30 students. The data collecting in this research uses the implementation test and expert judgment by using questionnaire sheet and competition test with data analysis technique using descriptive analysis. The results of research that obtained based on validator assessment that is user lecturer, therapist, masseur, and media expert, are in “Good” category. The result of usage assessment and competition test from students shows in “Good” category. Based on this data, it can be conlcuded that the developing of text book of treatment and injuries therapy in sports is feasible and effective to be used.